Energy Efficiency for Florida Aquaculture Facilities: Energy Use Audit - Jordan Neff; Eric Jon Cassiano; Micah Alo; Craig Watson (EDIS)
The energy consumption on aquaculture facilities can account for a large portion of on-farm operational costs. Energy associated with keeping aquatic plants and animals alive contributes to the total cost of operation. Even on a moderately sized farm, excessive energy consumption can be a limiting factor in the success of an aquaculture business. When recirculating aquaculture systems and indoor climate-controlled production methods are used, the cost of energy can be as large as the costs associated with labor and feed. Evaluating energy use on a facility allows for the opportunity to identify areas where energy may be used more efficiently. Increasing energy efficiency can help reduce overall operational costs and increase profitability. This publication is one in a series that details techniques and methods for reducing energy consumption on aquaculture farms.